Neuroprotective Evaluation of Murraya Carbazoles: In Vitro and Docking Insights into Their Anti-AChE and Anti-Aβ Activities - Himadri Sharma; Niti Sharma; Seong Soo A. An (Molecules)
The present study investigated the neuroprotective potential of the Murraya carbazole derivatives murrayanol, mahanimbine, murrayafoline A, and 9-methyl-9H-carbazole-2-carbaldehyde using in silico and in vitro assays. The pharmacokinetic properties and potential toxicity (ADME/T) of the carbazole derivatives were assessed to evaluate their prospects as up-and-coming drug candidates. Molecular docking was used to investigate the interactions of the compounds with Aβ (PDB: 1IYT, 2BEG, and 8EZE) and AChE receptors (PDB: 4EY7 and 1C2B). The results from the in vitro assays were used to validate and support the findings from the in silico assays. The compounds demonstrated significant inhibition of acetylcholinesterase (AChE), a key target in neurodegenerative disorders. Murrayanol and mahanimbine presented superior inhibitory activity (IC50 ~0.2 μg/mL), outperforming the reference drug, galantamine. The inhibition mechanisms were competitive (murrayanol, murrayafoline A, and 9-methyl-9H-carbazole-2-carbaldehyde) and non-competitive (mahanimbine), supported by low Ki values and strong docking affinities. The compounds also proved effective in reducing Aβ fibrillization (murrayanol: 40.83 ± 0.30%; murrayafoline A: 33.60 ± 0.55%, mahanimbine: 27.68 ± 2.71%). These findings highlight Murraya carbazoles as promising scaffolds for multifunctional agents in AD therapy. Further optimization and mechanistic studies are warranted to advance their development into clinically relevant neuroprotective agents.